Transaction Document Security Protection In The Form Of Image File, Jpg or Tif Interbank Transfer Using Steganography And Cryptography - Basuki, Sucipto; Anugrah, Reksa (Pandawan Sejahtera Indonesia, 2019)
Information security process can be done by hiding the information on other media or by certain methods, so that other people do not realize there is some information in the media. Technique known as Steganography and Cryptography. Steganography is a technique to hide or disguise the existence of secret messages in the media reservoirs. While Cryptography disguise the meaning of a message, but do not hide that there is a message. In a bank cannot be separated in the presence of inter-bank transactions which transfer if the transfer interbank transactions done in branch offices and nominal transaction exceeds the transaction limit branch offices will require official approval in the upper branch. How do I prove the authenticity of the document transfer transaction? Therefore, a company in the banking sector needs to be a medium to prove the validity of the document sent by the branch transaction. In this case the author has designed an application with a blend of steganography and cryptography techniques that can be used in testing the validity of the transaction document. By using steganographic techniques undercover in a media that has brought and cryptographic key assignment as random, then the document that is sent in the branch office can be proved.